The larval, pupal and mitogenomic characteristics of Agrilus adelphinus Kerremans, 1895 (Coleoptera, Buprestidae) from China - Huang, Xuyan; Gan, Yujie; Wang, Lei; Xu, Yanying; Wei, Zhonghua; Shi, Aimin (ZooKeys, 2023)
In this study, the larva and pupa of Agrilus adelphinus are described and illustrated. DNA barcoding ( COI gene) was used to associate the larval and pupal stages with adults based on the maximum-likelihood method. In the resulting phylogenetic tree, species from the same species-group were found to be clustered on a branch with high support value. To better understand A. adelphinus , the complete mitochondrial genome of this species was also sequenced and annotated. Comparing this genome to the known mitogenomes of Agrilus species, the newly sequenced genome is shorter, with 15,732 bp. However, its whole mitogenome composition and gene orientation were consistent with that of most species of Buprestidae. In the mitogenome of A. adelphinus , the ATGATAG sequence was observed between ATP8 and ATP6 , which is ATGATAA in other insect mitogenomes. Leu2, Phe, Ile, Gly, and Ser2 were the five most frequently encoded amino acids. The results further prove that DNA barcoding can remove the limitation of traditional taxonomy which cannot identify to species all developmental stages. This study also provides valuable molecular and morphological data for species identification and phylogenetic analyses of the genus Agrilus .